Corrections to “Research on Underwater Small Target Detection Technology Based on Single-Stage USSTD-YOLOv8n” - Weiguo Yi; Jinwei Yang; Lingwei Yan (IEEE Access)
Presents corrections to the paper, (Corrections to “Research on Underwater Small Target Detection Technology Based on Single-Stage USSTD-YOLOv8n”).